Construction of Antibacterial N‐Halamine Polymer Nanomaterials Capable of Bacterial Membrane Disruption for Efficient Anti‐Infective Wound Therapy - Gao, Yangyang; Song, Nan; Liu, Wenxin; Dong, Alideertu; Wang, Yan‐Jie; Yang, Ying‐Wei (Macromolecular bioscience, 2019)
The increasing occurrence of bacterial infection at the wound sites is a serious global problem, demanding the rapid development of new antibacterial materials for wound dressing to avoid the abuse of antibiotics and thereby antibiotic resistance. In this work, the authors first report on antibacterial N‐halamine polymer nanomaterials based on a strategic copolymerization of 3‐allyl‐5,5‐dimethylhydantoin (ADMH) and methyl methacrylate (MMA), which exhibits in vitro and in vivo antimicrobial efficacy against pathogenic bacteria including Staphylococcus aureus and Escherichia coli. Particularly, when a biological evaluation is run for wound therapy, the N‐halamine polymer nanomaterials exhibit a powerful antibacterial efficiency and wound healing ability after a series of histological examination of mouse wound. After the evaluation of biological and chemical surroundings, the proposed four‐stage mechanism suggests that, with unique antibacterial NCl bonds, the N‐halamine polymer nanomaterials can disrupt the bacterial membrane, as a result causing intracellular content leaked out and thereby cell death. Based on the synergistic action of antibacterial and wound therapy, the N‐halamine polymer nanomaterials are expected to be promising as wound dressing materials in medical healing and biomaterials. N‐Halamine polymer nanomaterial‐based wound dressing is designed and has addressed a good wound therapy efficiency in skin tissue–related bacterial infections depending on antibacterial function of NCl bonds. A proposed four‐step mechanism unlocks a detailed antibacterial action and therapy process to the use of the N‐halamine polymer nanomaterials as wound dressings in a biological and chemical surrounding.